Particle-based methods fundamentals and applications - Oñate, E.; Owen, D. R. J. (Computational Methods in Applied Sciences, 2011)
This book contains 11 chapters written by relevant scientists in the field of particle-based methods and their applications in engineering and applied sciences. The chapters cover most particle-based techniques used in practice including the discrete element method, the smooth particle hydrodynamic method and the particle finite element method. The book will be of interest to researchers and engineers interested in the fundamentals of particle-based methods and their applications.